Mental Fatigue Prior to Aerobic Exercise Reduces Exercise Pleasure and Negatively Affects Implicit Attitudes Toward Future Exercise. Issue 3 (June 2022) - Pessoa, Felipe de Azevedo; Pereira, Lucas Camilo; de Oliveira Araújo, Andressa; Oliveira, Gledson Tavares Amorim; Pereira, Daniel Carvalho; Elsangedy, Hassan Mohamed
We investigated the effects of mental fatigue (MF) on affective responses during an aerobic exercise session at moderate intensity. We submitted 12 insufficiently active adults (50% women; M age = 24.9 years, SD = 3.0; M BMI = 24.3 kg/m 2 ; SD = 2.6) to two 30-minute pre-exercise conditions: an MF condition (Stroop Color-Word task) and a control condition (watching a documentary) prior to their performance of 20 minutes of aerobic treadmill exercise at 40–59% of heart rate reserve. The minimum washout interval between conditions was two days. Perceived MF and motivation to perform physical exercise were assessed before and after conditions with a visual analog scale of 100 mm. We assessed participants' affective and exertion responses with the Feeling Scale, Rating of Perceived Exertion (RPE) and heart rate during every two minutes of physical exercise. Implicit attitudes toward physical exercise were assessed by the Implicit Association Test before the MF and control conditions and after the physical exercise session. The participants in the MF condition reported lower pleasure ( M difference = −1.57, 95% CI = −2.64 to −0.50, d = 0.93, p = .008) and higher exertion (RPE) ( M difference = 1.16, 95% CI = 0.04 to 2.27, d = 0.66, p = .043) compared to those in the control condition. Participants who experienced MF also reported a more negative implicit attitude toward physical exercise than in the control condition ( β = −0.47, 95% CI= −0.73 to −0.21, d = 1.41, p < .001). While these findings should be cross-validated in subsequent research with a larger and more diverse participant sample, there appears to be value in minimizing pre-exercise mental fatigue to avoid negative MF effects on the exercisers' affective experience.